Method for producing metal-loaded chemically modified cellulose fiber
By mixing chemically modified cellulose fibers with metal and water, supporting the uniform distribution of metals on the fibers, the problems of instability in the prior art of fiber deodorizing function and difficult to control shape are solved, and efficient deodorizing, antibacterial, antiviral and anti-allergicity are achieved, suitable for a variety of products, and the production cost and time are reduced.
Patent Information
- Application Number
- JP2021156541
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-27
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-09-27
AI Technical Summary
In the prior art, the deodorizing function of metal supported zeolite-containing cellulose fibers is not stable enough, and the fiber shape is difficult to control, which cannot meet the needs of efficient deodorizing and safety.
By mixing chemically modified cellulose fibers (in which some of the hydroxyl groups are replaced by hydroxymethyl groups, phosphate groups, hydroxyl groups, ketone groups or acyl groups) with metal and water, ensuring the concentration of cellulose fibers reaches 20% or higher, supporting the uniform distribution of metals on the fibers, thereby improving the deodorizing, antibacterial, antiviral and antiallergicity of the fibers.
The efficient deodorizing function is achieved and the fiber is given antibacterial, antiviral and antiallergicity. The high concentration of fiber can provide efficient functions under small amounts of addition. It is suitable for a variety of products, reducing production costs and time and avoiding possible yield reductions during the concentration process.
Smart Images

Figure 0007650769000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a method for producing a metal-loaded chemically modified cellulose fiber, and more particularly to a method for producing a metal-loaded chemically modified cellulose fiber having deodorizing, antibacterial, antiviral and antiallergenic functions. [Background technology]
[0002] Various studies have been conducted on fibers with deodorizing properties. For example, woven fabrics, nonwoven fabrics, or papers have been reported in which inorganic porous crystals such as zeolite are contained inside hydrophilic polymers such as natural cellulose, and metals such as silver and copper are supported on the zeolite (Patent Document 1). In addition, metal ion-containing cellulose fibers have been reported in which one or more metal ions selected from Ag, Au, Cu, etc. are contained in carboxymethylated cellulose fibers (Patent Document 2). [Prior art documents] [Patent documents]
[0003] [Patent Document 1] Patent No. 4149066 [Patent Document 2] JP 2019-199518 A Summary of the Invention [Problem to be solved by the invention]
[0004] However, the fiber described in Patent Document 1 has a problem that the zeolite is easily dropped off and does not fully exhibit the deodorizing function because the zeolite is physically supported within the cellulose fiber, and also has a problem that the shape of the fiber (diameter, length) cannot be controlled. In contrast, the fiber described in Patent Document 2 is a fiber with excellent deodorizing properties and safety. The present invention aims to provide a new method for producing a fiber that exhibits a deodorizing power comparable to or superior to that of the fiber described in Patent Document 2. [Means for solving the problem]
[0005] As a result of intensive research, the present inventors have found that a fiber with high deodorizing properties can be obtained by mixing chemically modified cellulose fibers in which a part of the hydroxyl groups of the cellulose fibers is substituted with one or more selected from carboxymethyl groups, phosphate groups, carboxyl groups, carbonyl groups, and acyl groups, with metal and water, and setting the concentration of the chemically modified cellulose fibers in the mixture to 20 mass% or more. Furthermore, it has been found that this fiber has not only high deodorizing properties, but also antibacterial properties, antiviral properties, and antiallergenic properties. In addition, since the obtained metal-supported chemically modified cellulose fibers have a high concentration, when they are blended into various articles to impart functions such as deodorizing properties to the articles, they can impart high functions even with a small amount of blended compared to conventional fibers. The present invention includes the following. [1] A method for producing metal-supported chemically modified cellulose fibers, comprising the steps of: The method includes a step of mixing chemically modified cellulose fibers, a metal, and water to support the metal on the chemically modified cellulose fibers, The chemically modified cellulose fiber is a fiber in which a portion of the hydroxyl groups of a cellulose fiber is substituted with one or more groups selected from a carboxymethyl group, a phosphate group, a carboxyl group, a carbonyl group, and an acyl group; the concentration of the chemically modified cellulose fiber in the mixture of the chemically modified cellulose fiber, the metal, and water in the supporting step is 20% by mass or more; The method according to claim 1, wherein the average fiber diameter of the metal-loaded chemically modified cellulose fibers is 1 μm or more. [2] The method according to [1], wherein the step of supporting comprises adding, under stirring, an aqueous solution containing metal ions to the chemically modified cellulose fibers. [3] The method according to [1] or [2], wherein the metal is one or more selected from Cu, Ag, Au, Pt, Pd, Ni, Mn, Fe, Ti, Al, or Zn. [4] The method according to any one of [1] to [3], wherein the chemically modified cellulose fiber is a carboxymethylated cellulose fiber. [5] The method according to any one of [1] to [4], wherein the metal is Cu. [6] The method according to any one of [1] to [5], wherein the metal-supported chemically modified cellulose fiber has a volume-based median diameter of 5 mm or less. Effect of the Invention
[0006] The present invention provides a method for producing metal-loaded chemically modified cellulose fibers that not only have high deodorizing properties but also have antibacterial, antiviral, and antiallergen functions. The metal-loaded chemically modified cellulose fibers obtained by the present invention can be blended with, for example, paper, nonwoven fabric, film, various resins, ceramics, cosmetics, paints, etc. to produce various products with the above-mentioned effects. In particular, the metal-loaded chemically modified cellulose fibers obtained by the manufacturing method of the present invention have an advantage that they can impart high effects to various products with a small amount of blending because they have a high concentration. When low-concentration fibers are used, it is necessary to blend a large amount of fibers with the product in order to achieve the desired effects in various products. However, depending on the product or application, it may not be possible to blend a large amount of fibers, and as a result, it may be difficult to produce a product with high deodorizing properties. The high-concentration metal-loaded chemically modified cellulose fibers obtained by the manufacturing method of the present invention can impart high effects even with a small amount of blending, so they are advantageous for application to various products that were difficult to produce for the above-mentioned reasons. The high-concentration fibers obtained by the present invention can reduce the cost and time required for concentration compared to low-concentration fibers. In addition, when concentration is not required, it is possible to avoid a decrease in yield that may occur during concentration. Such fibers are suitable for imparting the above-mentioned effects by being blended with, for example, films, oil-based products such as various resins, ceramics, paints, etc. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0007] The present invention provides a method for producing a metal-loaded chemically modified cellulose fiber, which includes a step of mixing a chemically modified cellulose fiber, a metal, and water to load the metal on the chemically modified cellulose fiber. In this method, the chemically modified cellulose fiber is a fiber in which some of the hydroxyl groups of the cellulose fiber have been substituted with one or more groups selected from a carboxymethyl group, a phosphate group, a carboxyl group, a carbonyl group, and an acyl group, and the concentration of the chemically modified cellulose fiber in the mixture of the chemically modified cellulose fiber, the metal, and water in the loading step is 20 mass% or more.
[0008] <Chemically modified cellulose fiber> The chemically modified cellulose fiber used in the manufacturing method of the present invention is a fiber in which a part of the hydroxyl groups of the cellulose fiber is substituted with one or more groups selected from a carboxymethyl group, a phosphate group, a carboxyl group, a carbonyl group, and an acyl group. Among these, the carboxymethyl group and the carboxyl group are preferred because they increase the amount of metal carried, and the carboxymethyl group is more preferred. The chemically modified cellulose may be in the form of a salt. Examples of the salt of the chemically modified cellulose include metal salts such as the sodium salt of the chemically modified cellulose.
[0009] The chemically modified cellulose fibers used in the present invention are preferably fibers having an average fiber diameter of 1 μm or more. By using chemically modified cellulose fibers having an average fiber diameter of 1 μm or more, the average fiber diameter of the obtained metal-supported chemically modified cellulose fibers can be made 1 μm or more. Chemically modified cellulose fibers made from pulp-derived cellulose and having an average fiber diameter of 1 μm or more are sometimes called chemically modified pulp.
[0010] The upper limit of the average fiber diameter of the chemically modified cellulose fibers is not particularly limited. It is usually about 100 μm. Therefore, the average fiber diameter of the chemically modified cellulose fibers is preferably 1 to 100 μm, more preferably 10 to 100 μm, and even more preferably 30 to 90 μm. The average fiber length of the chemically modified cellulose fibers is not particularly limited, but is usually about 0.1 to 10 mm. The average fiber diameter and average fiber length of the chemically modified cellulose fibers can be measured by analyzing 200 randomly selected fibers using an optical microscope or a microscope, and calculating the average.
[0011] Chemically modified cellulose fibers can be made into fibers with an average fiber diameter of less than 1 μm (sometimes called cellulose nanofibers (CNF)) by using a defibrating device such as a high-pressure homogenizer, but in the present invention, fibers with an average fiber diameter of 1 μm or more are used as the chemically modified cellulose fibers, rather than CNFs. By using fibers with an average fiber diameter of 1 μm or more as the chemically modified cellulose fibers and producing metal-supported chemically modified cellulose fibers with an average fiber diameter of 1 μm or more, it is possible to obtain the advantage that the fibers can be easily incorporated into various products. Furthermore, by making the average fiber diameter 1 μm or more, it is possible to reduce costs during production and transportation, and the production yield is also good.
[0012] <Raw material for chemically modified cellulose fibers> The type of cellulose raw material for producing chemically modified cellulose fibers is not particularly limited. Cellulose is a polysaccharide with a structure in which D-glucopyranose (also simply called "glucose residue" or "anhydrous glucose") is linked by β-1,4 bonds, and is generally classified into natural cellulose, regenerated cellulose, fine cellulose, microcrystalline cellulose with non-crystalline regions removed, etc., based on the origin and manufacturing method, etc., and in the present invention, any of these celluloses can be used as the raw material for chemically modified cellulose fibers.
[0013] Examples of natural cellulose include bleached or unbleached pulp, linters, refined linters, and cellulose produced by microorganisms such as acetic acid bacteria. The raw material for bleached or unbleached pulp is not particularly limited, and examples thereof include wood, cotton, straw, bamboo, hemp, jute, kenaf, etc. The method for producing bleached or unbleached pulp is also not particularly limited, and examples thereof include mechanical methods, chemical methods, or methods that combine the two. Examples of bleached or unbleached pulp classified according to the production method include mechanical pulp (thermomechanical pulp (TMP), groundwood pulp), chemical pulp (sulfite pulp such as softwood unbleached sulfite pulp (NUSP) and softwood bleached sulfite pulp (NBSP); kraft pulp such as softwood unbleached kraft pulp (NUKP), softwood bleached kraft pulp (NBKP), hardwood unbleached kraft pulp (LUKP), and hardwood bleached kraft pulp (LBKP)). Furthermore, in addition to papermaking pulp, dissolving pulp may be used. Dissolving pulp is chemically refined pulp, and is mainly used by dissolving it in chemicals, and is the main raw material for artificial fibers, cellophane, etc.
[0014] Examples of regenerated cellulose include cellulose dissolved in some solvent such as cuprammonium solution, cellulose xanthate solution, morpholine derivative, etc., and spun again. Examples of fine cellulose include those obtained by depolymerizing the above-mentioned natural cellulose, regenerated cellulose, or other cellulose-based materials (e.g., acid hydrolysis, alkali hydrolysis, enzymatic decomposition, explosive crushing, vibrating ball mill treatment, etc.), and those obtained by mechanically treating the above-mentioned cellulose-based materials.
[0015] <Method for producing cellulose fibers substituted with carboxymethyl groups> One type of chemically modified cellulose fiber is a fiber in which some of the hydroxyl groups of the cellulose fiber are replaced with carboxymethyl groups. Hereinafter, such fibers are referred to as carboxymethylated cellulose fibers. In addition, "carboxymethyl" is abbreviated as "CM." CM-modified cellulose fibers can generally be produced by treating the above-mentioned cellulose raw material with an alkali (mercerization), and then reacting the resulting mercerized cellulose (also called alkali cellulose) with a CM agent (also called etherification agent) (CM). Generally, a method in which both mercerization and CM are performed using water as a solvent (aqueous medium method) and a method in which both mercerization and CM are performed in an organic solvent or a mixed solvent of an organic solvent and water (solvent method) are used.
[0016] The mercerized cellulose fiber used in the present invention may be one produced by a conventional aqueous method or solvent method, but mercerized cellulose fiber produced by a method in which mercerization is carried out in a solvent mainly composed of water, as described below, and then mercerization is carried out in a mixed solvent of water and an organic solvent is preferred because it shows a higher effect when a metal is supported according to the present invention.
[0017] Mercerization is carried out in a solvent mainly composed of water means that the solvent used in mercerization contains water at a ratio of more than 50% by mass. The ratio of water in the solvent mainly composed of water is preferably 55% by mass or more, more preferably 60% by mass or more, more preferably 70% by mass or more, more preferably 80% by mass or more, even more preferably 90% by mass or more, and even more preferably 95% by mass or more. Most preferably, the solvent mainly composed of water is 100% by mass (i.e., water). Examples of solvents other than water in the solvent mainly composed of water (which can be used by mixing with water) include organic solvents used as a solvent in the subsequent CM process. For example, alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, isobutanol, and tertiary butanol, ketones such as acetone, diethyl ketone, and methyl ethyl ketone, as well as dioxane, diethyl ether, benzene, and dichloromethane can be mentioned, and these can be used alone or in a mixture of two or more kinds added to water in an amount of less than 50% by mass. The content of the organic solvent in the solvent mainly composed of water is preferably 45% by mass or less, more preferably 40% by mass or less, even more preferably 30% by mass or less, even more preferably 20% by mass or less, even more preferably 10% by mass or less, even more preferably 5% by mass or less, and more preferably 0% by mass.
[0018] Examples of the mercerizing agent include alkali metal hydroxides such as lithium hydroxide, sodium hydroxide, and potassium hydroxide, and any one or more of these can be used in combination. The mercerizing agent is not limited to these, but these alkali metal hydroxides can be added to the reactor as an aqueous solution of, for example, 1 to 60 mass%, preferably 2 to 45 mass%, and more preferably 3 to 25 mass%. In one embodiment, the amount of the mercerizing agent used is preferably 0.1 mol to 2.5 mol, more preferably 0.3 mol to 2.0 mol, and even more preferably 0.4 mol to 1.5 mol, relative to 100 g of cellulose (bone dry).
[0019] The amount of the solvent, mainly water, used during mercerization is not particularly limited as long as it allows stirring and mixing of the raw materials, but is preferably 1.5 to 20 times by mass, and more preferably 2 to 10 times by mass, relative to the cellulose raw material.
[0020] The mercerization treatment is carried out by mixing the cellulose raw material with a solvent mainly composed of water, adjusting the temperature of the reactor to 0 to 70°C, preferably 10 to 60°C, more preferably 10 to 40°C, adding an aqueous solution of a mercerizing agent, and stirring for 15 minutes to 8 hours, preferably 30 minutes to 7 hours, more preferably 30 minutes to 3 hours, thereby obtaining mercerized cellulose (alkali cellulose).
[0021] The pH during mercerization is preferably 9 or more, which allows the mercerization reaction to proceed. The pH is more preferably 11 or more, further preferably 12 or more, and may be 13 or more. There is no particular upper limit to the pH.
[0022] The mercerization can be carried out using a reactor capable of mixing and stirring the above-mentioned components while controlling the temperature, and various reactors conventionally used for mercerization reactions can be used. For example, a batch-type stirring device that stirs the above-mentioned components with two shafts is preferred from the viewpoints of both uniform mixing ability and productivity.
[0023] A mercerized cellulose fiber is obtained by adding a mercerized cellulose carboxylase agent (also called an etherification agent). Examples of the mercerized cellulose carboxylase agent include monochloroacetic acid, sodium monochloroacetate, methyl monochloroacetate, ethyl monochloroacetate, and isopropyl monochloroacetate. Among these, monochloroacetic acid or sodium monochloroacetate is preferred in terms of availability. The mercerized cellulose agent is preferably added in the range of 0.5 to 1.5 mol per anhydrous glucose unit of cellulose. The lower limit of the above range is more preferably 0.6 mol or more, and even more preferably 0.7 mol or more, and the upper limit is more preferably 1.3 mol or less, and even more preferably 1.1 mol or less. The mercerized cellulose agent is not limited thereto, but can be added to the reactor as an aqueous solution of, for example, 5 to 80 mass %, more preferably 30 to 60 mass %, or can be added in a powder state without dissolving.
[0024] The molar ratio of the mercerizing agent to the carboxymethylating agent (mercerizing agent / carboxymethylating agent) is generally 0.9 to 2.45 when monochloroacetic acid or sodium monochloroacetate is used as the carboxymethylating agent. The reason is that if it is less than 0.9, the carboxymethylating reaction may be insufficient, and unreacted monochloroacetic acid or sodium monochloroacetate may remain and be wasted, and if it exceeds 2.45, a side reaction between the excess mercerizing agent and monochloroacetic acid or sodium monochloroacetate may proceed, resulting in the production of an alkali metal glycolate, which may be uneconomical. The concentration of the mercerized cellulose in the carboxymethylating reaction is not particularly limited, but is preferably 1 to 40% (w / v) from the viewpoint of increasing the effective utilization rate of the carboxymethylating agent.
[0025] At the same time as the addition of the CM agent, or before or immediately after the addition of the CM agent, an organic solvent or an aqueous solution of an organic solvent can be appropriately added to the reactor, or the organic solvent other than water during the mercerization treatment can be appropriately reduced by reducing pressure, etc., to form a mixed solvent of water and an organic solvent. As described above, in the CM reaction, it is preferable to use a mixed solvent of water and an organic solvent as the solvent. The timing of adding or reducing the organic solvent may be any time between the end of the mercerization reaction and immediately after the addition of the CM agent, and is not particularly limited, but is preferably within 30 minutes before or after the addition of the CM agent, for example.
[0026] Examples of organic solvents used in the mixed solvent during the CM reaction include alcohols such as methanol, ethanol, n-propyl alcohol, isopropyl alcohol, n-butanol, isobutanol, and tertiary butanol, ketones such as acetone, diethyl ketone, and methyl ethyl ketone, as well as dioxane, diethyl ether, benzene, and dichloromethane, and it is preferable to use a mixture of these alone or a mixture of two or more of them with water as the solvent during the CM reaction. Among these organic solvents, monohydric alcohols having 1 to 4 carbon atoms are preferred, and monohydric alcohols having 1 to 3 carbon atoms are more preferred, because they have excellent compatibility with water.
[0027] The ratio of the organic solvent in the mixed solvent during CM is preferably 20 to 99 mass%, more preferably 30 to 99 mass%, even more preferably 40 to 99 mass%, even more preferably 45 to 99 mass%, and even more preferably 50 to 99 mass%, of the total of water and organic solvent.
[0028] The reaction medium for CM (a mixed solvent of water and an organic solvent, etc., not containing cellulose) preferably has a lower proportion of water (in other words, a higher proportion of organic solvent) than the reaction medium for mercerization. By satisfying this range, it is possible to maintain a high degree of crystallinity while increasing the degree of CM substitution of the resulting CM-modified cellulose fiber, thereby enhancing the effects of the present invention and enabling efficient production of CM-modified cellulose fiber. In addition, when the reaction medium for CM has a lower proportion of water (a higher proportion of organic solvent) than the reaction medium for mercerization, there is also the advantage that a mixed solvent for the CM-modification reaction can be formed by the simple means of adding a desired amount of organic solvent to the reaction system after the completion of the mercerization reaction when transitioning from the mercerization reaction to the CM-modification reaction.
[0029] A mixed solvent of water and an organic solvent is prepared, and the CM agent is added to the mercerized cellulose, followed by stirring for 15 minutes to 4 hours, preferably for about 15 minutes to 1 hour, while maintaining a constant temperature, preferably in the range of 10 to 40°C. The liquid containing mercerized cellulose and the CM agent are preferably mixed in several batches or by dropwise addition, in order to prevent the reaction mixture from becoming too hot. After adding the CM agent and stirring for a certain period of time, the temperature is raised if necessary to a reaction temperature of 30 to 90°C, preferably 40 to 90°C, more preferably 60 to 80°C, and an etherification (CM) reaction is carried out for 30 minutes to 10 hours, preferably 1 hour to 4 hours, to obtain CM cellulose fiber.
[0030] In the mercerization, the reactor used in the mercerization may be used as it is, or a separate reactor capable of mixing and stirring the above-mentioned components while controlling the temperature may be used. After the reaction is completed, the remaining alkali metal salt may be neutralized with a mineral acid or an organic acid. If necessary, by-products such as inorganic salts and organic acid salts may be removed by washing with aqueous methanol, followed by drying, pulverization, and classification. Examples of devices used in dry pulverization include impact mills such as hammer mills and pin mills, media mills such as ball mills and tower mills, and jet mills. Examples of devices used in wet pulverization include homogenizers, mass colloiders, and pearl mills.
[0031] The CM substitution degree of the CM-modified cellulose fiber is preferably 0.01 or more, more preferably 0.05 or more, more preferably 0.10 or more, even more preferably 0.20 or more, and particularly preferably 0.30 or more, from the viewpoint of exerting the effect of the supported metal. Also, from the viewpoint of maintaining the shape of the fiber, it is preferably 0.60 or less, more preferably 0.50 or less, and even more preferably 0.40 or less. The CM substitution degree (also called the etherification degree) indicates the ratio of hydroxyl groups in the glucose residues constituting the cellulose that are substituted with CM ether groups (the number of CM ether groups per glucose residue). The CM substitution degree is sometimes abbreviated as DS. The CM substitution degree can be adjusted by controlling the amount of the CM agent to be reacted, the amount of the mercerizing agent, the composition ratio of water and the organic solvent, and the like. In particular, CM-modified cellulose fiber having a CM substitution degree of 0.30 or more while maintaining the shape of the fiber can be obtained, for example, by the above-mentioned production method (a method in which a solvent mainly consisting of water is used during mercerization and a mixed solvent of water and an organic solvent is used during CMization).
[0032] The method for measuring the degree of CM substitution is as follows: Weigh out approximately 2.0 g of sample and place it in a 300 mL Erlenmeyer flask with a stopper. Add 100 mL of a solution of 1000 mL of nitric acid methanol and 100 mL of special-grade concentrated nitric acid, and shake for 3 hours to convert the carboxymethylcellulose salt (CMC) to H-CMC (hydrogen-type carboxymethylcellulose). Weigh out 1.5 to 2.0 g of the bone-dry H-CMC and place it in a 300 mL Erlenmeyer flask with a stopper. Moisten the H-CMC with 15 mL of 80% methanol, add 100 mL of 0.1 N-NaOH, and shake at room temperature for 3 hours. Using phenolphthalein as an indicator, back-titrate the excess NaOH with 0.1 N-H2SO4, and calculate the degree of CM substitution (DS value) using the following formula. A = [(100 × F'-0.1N-H2SO4 (mL) × F) × 0.1] / (bone dry mass of H-CMC (g)) CM substitution degree=0.162×A / (1-0.058×A) F': Factor of 0.1N-H2SO4 F: Factor of 0.1N NaOH.
[0033] The carboxymethyl cellulose fiber used in the present invention preferably has a B-type viscosity (25°C, 30 rpm) of 10 to 50 mPa·s when made into a 1% (w / v) aqueous dispersion, and more preferably 16 to 40 mPa·s. If the viscosity is extremely low or extremely high, the processability of the fiber when used as an internal or external additive (coating) to paper or film may deteriorate, and restrictions may be placed on the equipment that can be used for coating. The B-type viscosity of the carboxymethyl cellulose fiber can be measured using a BL-type viscometer (manufactured by Toki Sangyo Co., Ltd.) at 25°C and 30 rpm with a No. 1 rotor.
[0034] The degree of crystallinity of cellulose in the mercurized cellulose fiber used in the present invention is preferably 50% or more, more preferably 60% or more, of crystalline type I. The crystallinity of cellulose can be controlled by the concentration of the mercerizing agent, the temperature during treatment, and the degree of mercurization. Since a high concentration of alkali is used in mercerization and mercurization, cellulose type I crystals are easily converted to type II crystals, but the desired crystallinity can be maintained by adjusting the degree of modification, for example, by adjusting the amount of alkali (mercerizing agent) used. There is no particular upper limit to the degree of crystallinity of cellulose type I. In reality, the upper limit is thought to be about 90%.
[0035] It is generally known that a higher CM substitution degree increases the solubility of the fiber and decreases the degree of crystallinity. However, by using, for example, the above-mentioned production method (a method in which a solvent mainly made of water is used during mercerization and a mixed solvent of water and an organic solvent is used during CMization), it is possible to produce CM-modified cellulose fibers that have a high degree of CM substitution and a high proportion of crystalline type I.
[0036] The method for measuring the crystallinity of cellulose type I of carboxymethylcellulose fiber is as follows: The sample is placed in a glass cell and measured using an X-ray diffraction measuring device (LabX XRD-6000, manufactured by Shimadzu Corporation). The degree of crystallinity is calculated using the method of Segal et al., and is calculated from the diffraction intensity of the 002 plane at 2θ=22.6° and the diffraction intensity of the amorphous part at 2θ=18.5° using the diffraction intensity of the X-ray diffraction pattern at 2θ=10° to 30° as the baseline, according to the following formula: Xc = (I002c - Ia) / I002c x 100 Xc = Crystallinity of cellulose type I (%) I002c: Diffraction intensity at 2θ=22.6°, 002 plane Ia: 2θ=18.5°, diffraction intensity of the amorphous part.
[0037] It is preferred that the carboxylated cellulose fibers used in the present invention maintain at least a part of their fibrous shape even when dispersed in water, i.e., when an aqueous dispersion of the carboxylated cellulose fibers is observed under an electron microscope, a fibrous substance can be observed, and when the carboxylated cellulose fibers are measured by X-ray diffraction, a peak of cellulose type I crystals can be observed.
[0038] <Cellulose fiber with introduced phosphate groups> One type of chemically modified cellulose fiber is a fiber in which a phosphoric acid group is introduced into a part of the hydroxyl group of the cellulose fiber. Hereinafter, such a fiber is called phosphorylated cellulose fiber. The phosphorylated cellulose fiber can be obtained by introducing a phosphoric acid group derived from a phosphoric acid compound into the cellulose fiber by mixing a powder or an aqueous solution of a phosphoric acid compound with the above-mentioned cellulose raw material, or by adding an aqueous solution of a phosphoric acid compound to a slurry of the cellulose raw material. Examples of the phosphoric acid compound include phosphoric acid, polyphosphoric acid, phosphorous acid, hypophosphorous acid, phosphonic acid, polyphosphonic acid, and esters or salts thereof. Specific examples include, but are not limited to, phosphoric acid, sodium dihydrogen phosphate, disodium hydrogen phosphate, trisodium phosphate, sodium phosphite, potassium phosphite, sodium hypophosphite, potassium hypophosphite, sodium pyrophosphate, sodium metaphosphate, potassium dihydrogen phosphate, dipotassium hydrogen phosphate, tripotassium phosphate, potassium pyrophosphate, potassium metaphosphate, ammonium dihydrogen phosphate, diammonium hydrogen phosphate, triammonium phosphate, ammonium pyrophosphate, and ammonium metaphosphate. The phosphoric acid group derived from a phosphoric acid compound can be introduced into the cellulose by using one or more of these in combination. In this specification, the phosphoric acid group derived from a phosphoric acid compound includes a phosphoric acid group, a phosphorous acid group, a hypophosphorous acid group, a pyrophosphate group, a metaphosphate group, a polyphosphate group, a phosphonic acid group, and a polyphosphonic acid group. Phosphorylated cellulose fibers include cellulose fibers having one or more of these phosphoric acid groups introduced into the molecular chain. When reacting a cellulose raw material with a phosphoric acid compound, it is desirable to use the phosphoric acid compound as an aqueous solution, since this allows the reaction to proceed uniformly and increases the efficiency of introduction of the above groups, and in this case, the pH of the aqueous solution is preferably pH 3 to 7. A nitrogen-containing compound such as urea may also be added.
[0039] The degree of substitution of phosphate groups per glucose unit in phosphorylated cellulose fibers (hereinafter simply referred to as "phosphate group substitution degree") is preferably 0.001 or more and less than 0.40. The degree of phosphate group substitution per glucose unit can be measured by the following method: A slurry of phosphorylated cellulose fibers with a solid content of 0.2% by mass is prepared. A strongly acidic ion exchange resin (Amberjet 1024; Organo Corporation, conditioned) is added to the slurry in an amount of 1 / 10 by volume, and the slurry is shaken for 1 hour. The slurry is then poured onto a mesh with 90 μm openings to separate the resin from the slurry, thereby obtaining hydrogen-type phosphorylated cellulose fibers. Next, 50 μL of 0.1 N sodium hydroxide solution is added to the slurry after treatment with the ion exchange resin once every 30 seconds, while measuring the change in the electrical conductivity value of the slurry. The amount of alkali (mmol) required in the region where the electrical conductivity drops sharply in the measurement results is divided by the solid content (g) in the slurry to be titrated to calculate the amount of phosphate groups (mmol / g) per 1 g of hydrogen-type phosphorylated cellulose fibers. Furthermore, the degree of phosphate group substitution (DS) per glucose unit of the phosphorylated cellulose fibers is calculated by the following formula: DS = 0.162 x A / (1-0.079 x A) A: Amount of phosphate groups per gram of hydrogen phosphorylated cellulose fiber (mmol / g).
[0040] <Cellulose fiber with carboxyl groups introduced> One type of chemically modified cellulose fiber is a fiber in which a carboxyl group has been introduced into some of the hydroxyl groups of the cellulose fiber. Hereinafter, such fibers are referred to as carboxylated cellulose fibers or oxidized cellulose fibers. Oxidized cellulose fibers can be obtained by oxidizing some of the hydroxyl groups of the pyranose ring of cellulose to carboxyl groups using a known method. Examples of the method for oxidizing cellulose include a method in which cellulose is oxidized in water using an oxidizing agent in the presence of an N-oxyl compound such as 2,2,6,6-tetramethylpiperidine-1-oxy radical (TEMPO) and a bromide and / or iodide, and a method in which cellulose is oxidized by contacting a cellulose raw material with a gas containing ozone as an oxidizing agent.
[0041] The amount of carboxyl groups in the oxidized cellulose fibers is preferably 0.4 to 3.0 mmol / g, more preferably 0.6 to 2.0 mmol / g, even more preferably 1.0 to 2.0 mmol / g, and even more preferably 1.1 to 2.0 mmol / g, based on the bone dry mass of the oxidized cellulose fibers. The amount of carboxyl groups in the oxidized cellulose fibers can be adjusted by controlling the reaction conditions, such as the amount of oxidizing agent added and the reaction time. The amount of carboxyl groups can be measured by the following method: 60 ml of a 0.5% by mass slurry (aqueous dispersion) of oxidized cellulose fiber is prepared, and a 0.1 M aqueous hydrochloric acid solution is added to adjust the pH to 2.5. A 0.05 N aqueous sodium hydroxide solution is then added dropwise and the electrical conductivity is measured until the pH reaches 11. The electrical conductivity is calculated using the amount of sodium hydroxide (a) consumed in the neutralization stage of the weak acid, where the change in electrical conductivity is gradual, using the following formula: Amount of carboxyl groups [mmol / g oxidized cellulose fiber] = a [ml] × 0.05 / mass of oxidized cellulose fiber [g].
[0042] <Carbonyl-substituted cellulose fiber> One type of chemically modified cellulose fiber is a fiber in which some of the hydroxyl groups of the cellulose fiber have been replaced with carbonyl groups (-C=O). Such fibers are called carbonylated cellulose fibers.
[0043] <Acyl-substituted cellulose fiber> One type of chemically modified cellulose fiber is a fiber in which some of the hydroxyl groups of the cellulose fiber are replaced with acyl groups. Such fibers are called acylated cellulose fibers. The acyl group is preferably an acyl group having 1 to 8 carbon atoms, and examples of the acyl group include a formyl group, an acetyl group, a propynyl group, a butyryl group, an isobutyryl group, a valeryl group, an isovaleryl group, a pivaloyl group, a hexanoyl group, an octanoyl group, and a benzoyl group.
[0044] <Method of manufacturing metal-loaded chemically modified cellulose fiber> In the method for producing a metal-loaded chemically modified cellulose fiber of the present invention, the above-mentioned chemically modified cellulose fiber, a metal, and water are mixed together to load the metal on the chemically modified cellulose fiber. In this case, the concentration of the chemically modified cellulose fiber in the mixture of the chemically modified cellulose fiber, the metal, and water is set to 20 mass% or more. "Loading a metal on the chemically modified cellulose fiber" refers to loading, binding, containing, or coordinating metal ions or metal particles on the chemically modified cellulose fiber.
[0045] The method of mixing the chemically modified cellulose fiber, the metal, and the water is not limited, but may be, for example, a previously prepared aqueous dispersion or slurry of the chemically modified cellulose fiber and an aqueous solution containing metal ions may be mixed, or a powder of the chemically modified cellulose fiber may be mixed with an aqueous solution containing metal ions, or a metal powder may be directly added to an aqueous dispersion or slurry of the chemically modified cellulose fiber and mixed with a stirrer, or a metal powder and water may be added to the powder of the chemically modified cellulose fiber and mixed with a stirrer. When mixing, it is preferable to perform the mixing under stirring. The stirring conditions are not particularly limited, and may be any condition that allows the chemically modified cellulose fiber, the metal, and the water to be mixed entirely.
[0046] When using an aqueous solution containing metal ions, the concentration is not particularly limited and may be appropriately adjusted so as to obtain the desired effect. The concentration is preferably such that 0.50 to 2.50 mmol of metal is present per 1 g of chemically modified cellulose fiber, and more preferably such that 1.00 to 2.00 mmol of metal is present per 1 g of modified cellulose fiber. In general, the higher the concentration of the aqueous solution containing metal ions, the higher the amount of metal supported on the chemically modified cellulose fiber tends to be.
[0047] The time for contacting the chemically modified cellulose fiber, the metal, and the water may be adjusted appropriately. For example, it may be 3 minutes to 3 hours, preferably 20 minutes to 1 hour, but is not limited thereto. During contact, it is preferable to continue stirring for the above contact time. The temperature during contact is not particularly limited, but is preferably 15 to 40°C.
[0048] The pH of the liquid containing the chemically modified cellulose fibers, the metal, and the water is not particularly limited, but since a low pH makes it difficult for metal ions to bond, a pH of 6 to 12 is preferable, a pH of 7 to 11 is more preferable, and a pH of 8 to 10 is particularly preferable.
[0049] The solids concentration of the chemically modified cellulose fiber in the mixture containing the chemically modified cellulose fiber, the metal, and water is 20% by mass or more. It is preferably 25% by mass or more, and can be 35% by mass or more. By increasing the concentration of the chemically modified cellulose fiber when it is brought into contact with the metal, the concentration of the obtained metal-supported chemically modified cellulose fiber can also be increased. When blended into various products, high-concentration metal-supported chemically modified cellulose fiber can impart high effects even when blended in small amounts, and is therefore advantageous when blended into products in which it is difficult to blend large amounts of fiber.
[0050] The metal is at least one selected from Cu, Ag, Au, Pt, Pd, Ni, Mn, Fe, Ti, Al, and Zn. Among these, Cu or Ag is preferred because it has higher antibacterial and antiviral effects. Cu is particularly preferred.
[0051] The average fiber diameter of the metal-supported chemically modified cellulose fiber is 1 μm or more. By setting the average fiber diameter of the metal-supported chemically modified cellulose to 1 μm or more, it is possible to obtain an advantage that the fiber can be easily incorporated into various products. In addition, since the average fiber diameter is not too small, it is possible to reduce the costs during production and transportation, and it is also possible to expect an improvement in yield. There is no particular upper limit to the average fiber diameter. It is usually about 100 μm. Therefore, the average fiber diameter of the metal-supported chemically modified cellulose fiber is preferably 1 to 100 μm, more preferably 10 to 100 μm, and even more preferably 30 to 90 μm. It can be said that the average fiber diameter of the metal-supported chemically modified cellulose fiber is usually about the same as the average fiber diameter of the chemically modified cellulose fiber before the metal is supported.
[0052] The average fiber length of the metal-supported chemically modified cellulose fiber is not particularly limited, but is usually about 0.1 to 10 mm. The average fiber diameter and average fiber length of the metal-supported chemically modified cellulose fiber can be measured by the same method as that for measuring the average fiber diameter and average fiber length of the chemically modified cellulose fiber described above.
[0053] The volumetric median diameter of the metal-loaded chemically modified cellulose fiber is preferably 5 mm or less, or 3 mm or less, since this improves processability. It is more preferably 1 mm or less, and even more preferably 200 μm or less. There is no particular restriction on the lower limit of the median diameter, but it is about 1 μm or more. The volumetric median diameter of the metal-loaded chemically modified cellulose fiber can be measured by the following method: The particle size distribution is measured using a laser scattering method, and the value at which the integrated value of the volume accumulation distribution is 50% is defined as the volume-based median diameter. For the measurement, for example, a device such as Mastersizer (registered trademark) 3000 manufactured by Spectris Corporation can be used.
[0054] The metal loading of chemically modified cellulose fibers can be confirmed by scanning electron microscope images and / or ICP emission spectrometry of the extract with strong acid. The presence of metal ions cannot be confirmed by scanning electron microscope images alone, but can be confirmed by combining scanning electron microscope images with element mapping or by using ICP emission spectrometry. In addition, when metal ions are reduced and exist as metal particles, the metal particles can also be confirmed by scanning electron microscope images or transmission electron microscope images.
[0055] The metal content in the metal-loaded chemically modified cellulose fiber obtained by the present invention is preferably 40 mg / g or more relative to the chemically modified cellulose fiber. By loading this amount, the deodorizing effect is enhanced, and antibacterial, antiviral, and antiallergenic properties are also expressed. Since the higher the content, the higher the effect generally is, the preferably 45 mg / g or more. There is no particular limit to the upper limit of the content. Since the effect is generally maximized at a content of about 60 mg / g, the upper limit of the content may be about 70 mg / g or less.
[0056] The content of metal contained in the metal-supported chemically modified cellulose fiber can be measured by the method described in the examples below. <Products containing metal-loaded chemically modified cellulose fibers> The metal-supported chemically modified cellulose fiber of the present invention not only has high deodorizing properties but also has antibacterial, antiviral and antiallergen functions, and various products having the above-mentioned effects can be produced by blending it with, for example, paper, nonwoven fabric, film, various resins, etc. Products containing the metal-supported chemically modified cellulose fiber of the present invention include, but are not limited to, hygiene materials such as masks and wet or dry wipe sheets, daily necessities, various cosmetics, etc.
[0057] In particular, the manufacturing method of the present invention can obtain metal-supported chemically modified cellulose fibers in a high concentration. When blended into various products, high-concentration metal-supported chemically modified cellulose fibers can provide high effects even when blended in small amounts, so they can be advantageously used in applications where blending large amounts of fibers has been difficult in the past. For example, they are advantageously blended into films, oil-based products such as various resins, ceramics, paints, etc.
[0058] The shape of the product is not particularly limited, but from the viewpoint of ease of processing and easy exertion of effects such as deodorization, a sheet shape such as paper, thin film, thin plate, film, woven fabric or nonwoven fabric is preferred. Examples of sheet-shaped products include, but are not limited to, the above-mentioned masks and wet or dry wipe sheets. In addition, when attempting to expand into various applications, the metal-supported chemically modified cellulose fiber may be in a liquid form dispersed in any liquid medium. For example, it may be a liquid paint, dispersant, shape retainer, etc. The liquid form allows external or internal addition to paper or film.
[0059] The amount of the metal-loaded chemically modified cellulose fiber to be blended in the product (absolute dry mass) can be adjusted appropriately depending on the application and purpose, and can be blended up to about 60 mass% for example. When the amount of metal loaded in the metal-loaded chemically modified cellulose fiber is high, even a small amount can be blended to impart an effect to the product, so the blending amount may be 10 mass% or less, 5 mass% or less, or 2 mass% or less. A small amount of the metal loaded in the product can suppress an increase in the cost of the product, and also has the advantage that the product can be manufactured while maintaining the original physical properties (strength, durability, color, etc.) of the product as much as possible. In consideration of sufficient expression of the effect, the lower limit of the blending amount in the product is preferably 0.1 mass% or more, and more preferably 1 mass% or more. According to the manufacturing method of the present invention, the metal-loaded chemically modified cellulose fiber can be obtained in a high concentration state, so that a small amount of the fiber can be blended to impart a large amount of fiber to various products without performing much concentration or performing no concentration at all. Fibers with a high concentration have the advantage that the cost and time required for concentration can be reduced compared to fibers with a low concentration. Another advantage is that it is possible to avoid a decrease in yield that may occur during concentration. EXAMPLES
[0060] [Example 1] 130 parts of water and 20 parts of sodium hydroxide dissolved in 100 parts of water were added to a twin-shaft kneader with the rotation speed adjusted to 100 rpm, and 100 parts of hardwood bleached kraft pulp (LBKP, manufactured by Nippon Paper Industries Co., Ltd.) was added based on the dry mass when it was dried at 100°C for 60 minutes. The mixture was stirred and mixed at 30°C for 90 minutes to prepare mercerized cellulose. 230 parts of isopropanol (IPA) and 60 parts of sodium monochloroacetate were further added while stirring, and after stirring for 30 minutes, the mixture was heated to 70°C and allowed to react for 90 minutes. The concentration of IPA in the reaction medium during the CM reaction was 50%. After the reaction, the mixture was neutralized with acetic acid until the pH reached 7, washed with aqueous methanol, deliquinated, dried, and pulverized to obtain carboxymethylcellulose fibers with a carboxymethylcellulose substitution degree of 0.34, a crystallinity of cellulose type I of 70%, and a B-type viscosity (BL-type viscometer (Toki Sangyo Co., Ltd.), 25°C, 30 rpm) of 38 mPa·s when dispersed in 1% (w / v) water. 1000 g (solid content 95%) of the produced carboxymethylcellulose fibers were placed in a stirrer (AT-55, Pacific Machinery Works Co., Ltd.), and while stirring, a 5 mass% copper sulfate aqueous solution in which copper sulfate pentahydrate (FUJIFILM Wako Pure Chemical Industries, Ltd.) was dissolved in water was added at 50 mL / min so that the amount of copper sulfate was equivalent to 1.00 mmol per 1 g of carboxymethylcellulose fibers. Finally, the concentration of carboxymethylcellulose fibers in the mixture of carboxymethylcellulose fibers and the copper sulfate aqueous solution was 27 mass%. After the addition was completed, stirring was continued for 10 minutes. The sample was then collected.
[0061] [Example 2] The same procedure as in Example 1 was carried out, except that an aqueous solution of copper sulfate adjusted to a concentration of 5% by mass was added at 100 mL / min.
[0062] [Example 3] The same procedure as in Example 1 was carried out, except that a 10% by mass aqueous copper sulfate solution was used.
[0063] [Example 4] 100 parts by mass (absolute dry mass) of the same hardwood bleached kraft pulp as that used in Example 1 was impregnated with a mixed aqueous solution of ammonium dihydrogen phosphate and urea to obtain 56 parts by mass of ammonium dihydrogen phosphate and 150 parts by mass of urea, and squeezed to obtain a chemical-impregnated pulp. The obtained chemical-impregnated pulp was dried in a dryer at 105°C to evaporate water. Then, it was heated for 10 minutes in a blower dryer set at 105°C to introduce phosphoric acid groups into the cellulose in the pulp. 5000 parts by mass of ion-exchanged water was poured into 100 parts by mass of the obtained phosphorylated cellulose, and the mixture was stirred to disperse uniformly, and then filtered and dehydrated to obtain a dehydrated sheet. This process was repeated twice. Next, the obtained dehydrated sheet was diluted with 5000 parts by mass of ion-exchanged water, and 1N aqueous sodium hydroxide solution was added little by little while stirring to obtain a pulp slurry with a pH of 12 to 13. The pulp slurry was then dehydrated to obtain a dehydrated sheet, after which 5000 parts by mass of ion-exchanged water was poured in, stirred to disperse uniformly, and then filtered and dehydrated to obtain a dehydrated sheet of phosphorylated cellulose. 1000 g (95% solids) of the phosphorylated cellulose fiber produced was placed in a mixer (AT-55, manufactured by Pacific Machinery Co., Ltd.), and while stirring, a 5% by mass copper sulfate aqueous solution in which copper sulfate pentahydrate (manufactured by Fujifilm Wako Pure Chemical Industries, Ltd.) was dissolved in water was added at 50 mL / min so that the amount of copper sulfate was equivalent to 1.00 mmol per 1 g of phosphorylated cellulose fiber. After the addition was completed, stirring was continued for 10 minutes, and then the sample was collected.
[0064] [Comparative Example 1] The same treatment as in Example 1 was carried out, except that the 5% by mass aqueous solution of copper sulfate was not added. [Comparative Example 2] The same treatment as in Example 1 was carried out, except that the cellulose fibers were not converted into CM and hardwood bleached kraft pulp was fed into the mixer.
[0065] [Washing, dehydration, and drying] The obtained samples of Examples 1 to 4 and Comparative Examples 1 and 2 were washed with three times the amount of water and dehydrated in a centrifugal dehydrator. A part of the collected cake was dried at 105° C. for 2 hours to prepare a dried sample used below.
[0066] [Measurement of average fiber diameter] Using a microscope, 200 randomly selected fibers were analyzed and the average fiber diameter was calculated.
[0067] [Median diameter measurement] Using a Spectris Mastersizer (registered trademark) 3000, particle size distribution was measured by a laser scattering method, and the value at which the integrated value of the volume accumulation distribution was 50% was taken as the median diameter (volume basis). In detail, the sample was added to the measurement section in water stirred at 3500 rpm so that the scattering intensity was about 10%, and the measurement was performed under the following conditions. Analysis: General purpose Analysis Sensitivity: Emphasis Light scattering model: Mie theory [Metal content measurement] Approximately 0.1 g of the dried sample was placed in a 50 mL beaker. Concentrated nitric acid (for quantifying trace metals) was transferred to another beaker, and then 10 mL was taken with a whole pipette and placed in the beaker containing the sample and left to stand for 30 minutes. The resulting sample liquid was passed through a syringe filter to remove the fiber content, and 1 mL of the filtered sample liquid was taken with a micropipette and added to 49 mL of ultrapure water and stirred (50-fold dilution). The metal content in the liquid was measured (unit: ppm) using an ICP-OES (Shimadzu Corporation: ICPE-9000), and the metal content in 1 g of carboxylated cellulose fiber was calculated using the following formula: Metal loading amount (mg / g) = (metal content in liquid (ppm) × 50 × 10 mL) / fiber amount in dried sample (g) / 1000 [Sheet manufacturing] Based on JIS P 8222, the following procedure is used to check the basis weight of a paper sheet for 100 g / m2. 2A hand-made sheet of about 100% was produced. Hardwood bleached kraft pulp (LBKP, manufactured by Nippon Paper Industries Co., Ltd.) and softwood bleached kraft pulp (NBKP, manufactured by Nippon Paper Industries Co., Ltd.) were mixed in a mass ratio of 8:2, and the Canadian standard freeness was adjusted to 420 ml using a single disc refiner (SDR). The pulp obtained was blended with the dried samples from each of the samples in Examples 1 to 4 and Comparative Examples 1 and 2 (the blending ratio was pulp:dry sample = 99:1 in terms of mass ratio of solids), and water was added to prepare a suspension with a solids concentration of 0.5 to 0.8%, and a sheet was produced using this suspension.
[0068] [Deodorization test] The manufactured sheet (basis weight: approx. 100 g / m 2 The deodorizing properties were evaluated using a 100 cm 2 The deodorizing test was conducted based on the SEK Mark Textile Product Certification Standard (JEC301, Japan Textile Evaluation Technology Council), and targeted hydrogen sulfide, which corresponds to the odor of excrement and food waste.
[0069] The odor reduction rate (%) was calculated from the following formula, with 70% or more being considered pass (◯) and less than 70% being considered fail (×). As a result, it was confirmed that the samples of Examples 1 to 4 were pass. Odor reduction rate (%) = (Sb - Sm) / Sb × 100 Sb: Average value of blank test Sm: average value of the measurements [Antibacterial test] The antibacterial properties were evaluated using the manufactured sheets. The weight of the sheets used in the antibacterial test was 0.4 g. Standard cotton cloth was used as a reference. The antibacterial test was performed using the bacterial liquid absorption method (a quantitative test method in which the test inoculum is directly inoculated onto the test specimen) specified in JIS L 1902. Two types of test bacteria, Staphylococcus aureus NBRC 12732 and Escherichia coli NBRC 3301, were used, and the viable cell count after 18 hours of culture was measured using the pour plate culture method. The test procedure is as follows. 1. Place 0.4 g of the test piece (above sheet) in a vial, drip 0.2 ml of test bacteria liquid (containing 0.05% surfactant (Tween 80)), and then close the vial. 2. Incubate the vials at 37°C for 18 hours. 3. Add 20 ml of washing solution to wash out the test bacteria from the test piece, and measure the number of live bacteria in the washing solution using the pour plate culture method or luminescence measurement method. 4. Calculate the antibacterial activity value according to the following formula: An antibacterial activity value of 2.0 or more means that the bacterial death rate is 99% or more. Antibacterial activity value = {log(viable bacteria count after incubation of control sample) - log(viable bacteria count immediately after inoculation of control sample)} - {log(viable bacteria count after incubation of test sample) - log(viable bacteria count immediately after inoculation of test sample)} From the above formula, an antibacterial activity value of 2.0 or more was rated as a pass (◯), and a value of less than 2.0 was rated as a fail (×).
[0070] [Antiviral test] The antiviral test was carried out according to JIS L 1922:2016, antiviral test method for textile products. The weight of the sheet used in the test was 0.4g, and a standard cotton cloth was used as the control sample. The feline calicivirus (Strain: F-9 ATCC VR-782) was used as the test virus species. The test procedure is as follows. 1. Place 0.4 g of the test piece (above sheet) in a vial, drip 0.2 ml of the test virus liquid, and then close the vial lid. 2. Leave the vial at 25°C for 2 hours. 3. Add 20 ml of washing solution to wash out the virus from the test piece, and calculate the infectivity value using the plaque assay method. 4. Calculate the antiviral activity value (Mv) using the following formula. Note that the JIS stipulates that there is an antiviral effect when Mv ≥ 2.0, and there is sufficient antiviral effect when Mv ≥ 3.0. Antiviral activity value (Mv) = Log(Vb)-Log(Vc) Mv: Antiviral activity value Log(Vb): Common logarithm of the infectivity titer of the control sample after 2 hours of exposure (average of three samples) Log(Vc): Common logarithm of the infectivity titer of the antiviral sample after 2 hours of action (average value of three samples) From the above formula, an antiviral activity value (Mv) of 2.0 or more was rated as pass (◯), and an antiviral activity value of less than 2.0 was rated as fail (×).
[0071] [Anti-allergen test] The manufactured sheet (basis weight: approx. 100 g / m 2 The anti-allergen properties were evaluated using the following procedure.
[0072] Purified Cry j1 (manufactured by Seikagaku Biobusiness Co., Ltd.) was dissolved in phosphate buffered saline (PBS) containing 0.05% Tween 20 to a concentration of 100 ng / mL to prepare a test solution. At room temperature, 0.2 g of the test piece (above sheet) was placed in a 15 ml plastic tube and contacted with 1 ml of the test solution. After leaving it to stand for 1 hour, the test piece was squeezed with fingers to extract the test solution, which was then centrifuged at 10,000 x g for 3 minutes, and the allergen concentration (Cry j1 concentration) in the supernatant was measured by sandwich ELISA. As a comparative control, the test solution alone was also measured.
[0073] The allergen concentration (Cry j1 concentration) was measured by sandwich ELISA under the following conditions. n=2 (2 wells) per sample Measuring equipment: MULTISKAN FC (Thermo) ·Measurement wavelength: 405nm The deactivation removal rate (%) was calculated from the following formula: The deactivation removal rate was calculated using Comparative Example 1 (no metal added) as a control. "Inactivation removal rate (%)" = [1 - (amount of allergen remaining in test sample) / (amount of allergen remaining in control sample)] x 100 From the above formula, a deactivation and removal rate of cedar pollen allergen (Cry j1) of 75% or more was deemed a pass (○), and a rate of less than 75% was deemed a fail (×).
[0074] [result] The results of the above tests are shown in Table 1. The samples of Examples 1 to 4 obtained by the production method of the present invention were found to have high deodorizing properties, as well as high antibacterial properties, antiviral properties, and antiallergenic properties.
[0075] [Table 1] [Industrial Applicability]
[0076] The metal-supported chemically modified cellulose fiber obtained by the manufacturing method of the present invention has deodorizing, antibacterial, antiviral, and antiallergenic properties, and is therefore suitable for manufacturing sanitary materials by blending it with materials such as paper, nonwoven fabric, film, and resin. It can also be blended with oil-based products such as various resins, ceramics, paints, and the like. In addition, the manufacturing method of the present invention has the advantage that the metal-supported chemically modified cellulose fiber can be obtained in a high concentration state, and the above-mentioned various effects can be imparted to various products by blending a small amount. In addition, compared to the case of using fibers with a low concentration, the cost and time required for concentration can be reduced, and a decrease in yield that may occur during concentration can be avoided.
Claims
1. A method for producing a metal-supported chemically modified cellulose fiber, comprising the steps of: The method includes a step of mixing chemically modified cellulose fibers, a metal, and water to bond ions of the metal to the chemically modified cellulose fibers, The chemically modified cellulose fiber is a fiber in which a portion of hydroxyl groups of a cellulose fiber is substituted with one or more groups selected from a carboxymethyl group, a phosphoric acid group, and a carboxyl group, the concentration of the chemically modified cellulose fiber in the mixture of the chemically modified cellulose fiber, the metal, and water in the step of bonding the metal ions is 20% by mass or more; The average fiber diameter of the metal-supported chemically modified cellulose fiber is 1 μm or more and 100 μm or less, the metal is Cu, The method, wherein mixing the chemically modified cellulose fiber with a metal and water includes mixing an aqueous solution containing metal ions with an aqueous dispersion or slurry of the chemically modified cellulose fiber, mixing a powder of the chemically modified cellulose fiber with an aqueous solution containing metal ions, adding metal powder to an aqueous dispersion or slurry of the chemically modified cellulose fiber and mixing it, or adding metal powder and water to the powder of the chemically modified cellulose fiber and mixing it.
2. 2. The method of claim 1, wherein mixing the chemically modified cellulose fiber, metal, and water comprises mixing, under agitation, an aqueous dispersion or slurry of the chemically modified cellulose fiber with an aqueous solution containing metal ions, or mixing the powdered chemically modified cellulose fiber with an aqueous solution containing metal ions.
3. The method according to claim 1 or 2, wherein the chemically modified cellulose fibers are carboxymethylated cellulose fibers.
4. The method according to any one of claims 1 to 3, wherein the volume-based median diameter of the metal-supported chemically modified cellulose fiber is 1 µm or more and 5 mm or less.
Citation Information
Patent Citations
JP1968007960B
Novel preparation of calcium carboxymethylcellulose
JP1992314701A
Absorbent article
JP2015043940A
Method for producing composite, and composite
JP2015221845A
Photothermal conversion material, photothermal conversion composition and photothermal conversion molded body
JP2019002004A